The Effect of Different Court Surfaces on Tennis Player Performance and Injury Risk: A Comparative Study - Jesus Rajkumar, N. C. (Journal of Neonatal Surgery, 2025)
This study aims to evaluate the influence of different tennis court surfaces hard, clay, and grass on player performance and injury risk. Thirty professional tennis players participated, playing matches on all three surfaces over a 12-week period. Performance metrics such as serve speed, rally duration, and unforced errors were collected. Injury reports and post-match fatigue levels were analysed to assess the impact of each surface on player health. Results indicate that clay courts result in longer rallies and greater endurance demands, while hard courts pose a higher injury risk, particularly to the lower limbs. Grass courts produced the shortest rallies but necessitated quicker reaction times. These findings provide valuable insights for players, coaches, and tournament organizers, highlighting the importance of surface selection in maximizing performance and minimizing injury risks.